2010
DOI: 10.1007/s12011-010-8872-1
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Growth in Mungbean (Phaseolus aureus Roxb.) by Selenium is Associated with Stimulation of Carbohydrate Metabolism

Abstract: The mungbean plants were grown hydroponically in the absence (control) or presence of 0.1, 0.25, 0.50 and 0.75 ppm selenium (as sodium selenate) for 10 days. The growth of shoots and roots increased with application of selenium with greater extent in shoots. With 0.5 and 0.75 ppm Se levels, the shoot growth was stimulated by 24% to 27% over control, respectively, while the roots showed a corresponding increase of 18-19%, respectively. The shoot-to-root ratio was enhanced significantly with Se application and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 33 publications
4
36
1
Order By: Relevance
“…Selenium increases carbohydrate or starch accumulation in chloroplasts as reported by several investigators (Malik et al, 2011;Hashem et al, 2013;Hajiboland et al, 2015).…”
Section: Starch and Sugarssupporting
confidence: 56%
“…Selenium increases carbohydrate or starch accumulation in chloroplasts as reported by several investigators (Malik et al, 2011;Hashem et al, 2013;Hajiboland et al, 2015).…”
Section: Starch and Sugarssupporting
confidence: 56%
“…However, there have been reports of beneficial effects at low Se doses on plant growth (Hartikainen, 2005;Lyons et al, 2009;PilonSmits et al, 2009;Rios et al, 2009;Yao et al, 2009;Malik et al, 2011). In the kenaf plants, the slight increase in dry biomass for the lowest doses was not statistically significant.…”
Section: Discussionmentioning
confidence: 91%
“…Increases in sucrose and total sugar concentration up to the 400 and 800 g ha −1 treatments may be due to the activity of carbohydrate metabolism enzymes. Malik et al (2011) observed that mung bean (Phaseolus aureus Roxb.) exposed to Se showed increased activity of amylases and invertases.…”
Section: Photoassimilates and Photosynthetic Pigmentsmentioning
confidence: 99%